The Effect Of Predict-Observe-Explain (POE) Learning Model On Students' Science Process Skills Biology In MTs Aisyiyah Binjai - Ismayanti Ismayanti; Indayana Febriani Tanjung; Khairuddin Khairuddin (Journal of Education and Teaching Learning, 2022)
This study aims to determine the effect of the Predict-Observe-Explain (POE) learning model on science process skills in biology learning. This research was conducted at MTs Aisyiyah Binjai in the academic year 2020/2021, and this research was conducted at the end of May to June 2021. The type of research carried out was descriptive quantitative research. In sampling the researchers took two classes, namely the experimental class with 32 students using the Predict-Observe-Explain (POE) learning model and the control class with 32 students. The research method was carried out by preparing research instruments, namely observation sheets and student worksheets, validating instruments with 2 validators, namely North Sumatra State Islamic University lecturers and data collection was carried out by direct observation using observation sheet guidelines to see students' science process skills. The population in this study were all biology students of class VIII MTs Aisyiyah Binjai. Based on the research conducted, it shows the influence of students' science process skills using the Predict-Observe-Explain (POE) learning model. Judging from the results of data processing science process skills students in the experimental class with a percentage of 74% while in the control class with a percentage of only 41%. So that the KPS value of students in the experimental class is higher than the control class.